NOVEL APPROACHES TO CREATING ECONOMIC SECURITY AT OLDER AGES AMID GROWING ECONOMIC VOLATILITY. (11th November 2018) - Weller, C
Abstract: Americans need more savings than in the past to pay for their retirement and to cover economic emergencies, especially as jobs and wages have become more volatile. Yet, wealth inequality has grown for decades, leaving a growing number of people both with the prospect of financial struggles in retirement and the inability to pay their bills when an emergency strikes. New policy responses try to address the dual problem of an insecure retirement and present-day financial struggles. Such policies include more efficient tax incentives to help people save for retirement, new ways to encourage emergency savings and targeted Social Security benefit improvements to directly counter the growing labor market volatility that people face. As a result, these policy interventions try to efficiently target the populations that are most in need of more economic security.